PENGARUH MOTIVASI BERWIRAUSAHA DAN LINGKUNGAN TERHADAP MINAT MAHASISWA BERWIRAUSAHA - Pril Ranto, Dwi Wahyu; Sarjita, Sarjita; Parawansa, Khofifah Indra (PRIMA EKONOMIKA, 2021)
This study aims to examine the effect of entrepreneurial motivation and the environment on students' interest in entrepreneurship. The population in this study were students of AMA YPK Yogyakarta. The sampling technique used was Convenience sampling. Which means that the researcher sees the reality and the respondent gets it. The results of this study indicate that the variables of entrepreneurial motivation and the environment have a significant effect on interest in entrepreneurship. The limitation of this study is the limited number of respondents so that the results of the study do not provide an overview of respondents who are truly interested in entrepreneurship. Keywords: Entrepreneurial motivation, environment, entrepreneurial intentions